Sickening or Healing the Heart? The Association of Ficolin-1 and Rheumatic Fever - Catarino, Sandra Jeremias; Andrade, Fabiana Antunes; Boldt, Angelica Beate Winter; Guilherme, Luiza; Messias-Reason, Iara Jose (Frontiers in Immunology, 2018)
Rheumatic fever (RF) and its subsequent progression to rheumatic heart disease (RHD) are chronic inflammatory disorders prevalent in children and adolescents in underdeveloped countries, and a contributing factor for high morbidity and mortality rates worldwide. Their primary cause is oropharynx infection by Streptococcus pyogenes, whose acetylated residues are recognized by ficolin-1. This is the only membrane-bound, as well as soluble activator molecule of the complement lectin pathway (LP). Although LP genetic polymorphisms are associated with RF, FCN1 gene’s role remains unknown. To understand this role, we haplotyped five FCN1 promoter polymorphisms by sequence-specific amplification in 193 patients (138 with RHD and 55, RF only) and 193 controls, measuring ficolin-1 serum concentrations in 78 patients and 86 controls, using ELISA. Patients presented lower ficolin-1 serum levels (p<0.0001) but did not differ according to cardiac commitment. Control’s genotype distribution was in the Hardy-Weinberg equilibrium. Four alleles (rs2989727: c.-1981A, rs10120023: c.-542A, rs10117466: c.-144A, rs10858293: c.33T), all associated with increased FCN1 gene expression in whole blood or adipose subcutaneous tissue (p=0.000001), were also associated with increased protection against the disease. They occur within the *3C2 haplotype, associated with an increased protection against RF (OR=0.41, p<0.0001) and with higher ficolin-1 levels in patient serum (p=0.03). In addition, major alleles of these same polymorphisms comprehend the most primitive *1 haplotype, associated with increased susceptibility to RF (OR=1.76, p<0.0001). Nevertheless, instead of having a clear-cut protective role, the minor c.-1981A and c.-144A alleles were also associated with additive susceptibility to valvar stenosis and mitral insufficiency (OR=3.75, p=0.009 and OR=3.37, p=0.027, respectively). All associations were independent of age, sex or ethnicity. Thus, minor FCN1 promoter variants may play a protective role against RF, by encouraging bacteria elimination as well as increasing gene expression and protein levels. On the other hand, they may also predispose the patients to RHD symptoms, by probably contributing to chronic inflammation and tissue injury, thus emphasizing the dual importance of ficolin-1 in both conditions.